Mortality due to Hodgkin's Lymphoma in the northeast region of Brazil in the years 2011-2020 - Botentuit, Raimundo Cezar Ribeiro (2023)
Objectives: To analyze mortality due to Hodgkin's Lymphoma in the Northeast region of Brazil, during the years 2011 to 2020. Methods: This is an epidemiological, retrospective study with a quantitative approach, whose data were collected through the website of the Department of Informatics of the SUS (DATASUS), which provides access to the online atlas of cancer mortality from the National Cancer Institute (INCA). Results: From 2011 to 2020, 1,141 Brazilians died due to Hodgkin's Lymphoma. The mortality rate showed a non-constant trend where in certain periods there was an increase in deaths and in other moments a reduction. Of the nine states in the Northeast region, Bahia was the state with the highest number of registered deaths, followed by Ceará, Pernambuco and Maranhão. Regarding age group, deaths are concentrated between 20-29 years. As for gender, males had the highest number of deaths. Conclusion: Hodgkin's Lymphoma is a curable neoplasm that still affects a large number of people, who consequently can die if the treatment has not caused it in the expected way. It is necessary to understand the aspects related to HL, to assist in the development of means to combat the disease that has, in large part, the cancellation of its unknown pathogenesis.